The Influence of trust on customer loyalty among food companies in Kenya - Khalayi, R. (Strathmore University, 2025)
This study explores the pivotal role of trust in influencing customer loyalty among food and beverage companies in Kenya. In the highly competitive food and beverage sector, establishing and maintaining customer loyalty is crucial for business sustainability and growth. This research sought to identify the key factors that build trust between consumers and companies and how these factors subsequently affect customer loyalty. A quantitative approach was employed, combining quantitative questionnaires to gather comprehensive data from customers and industry professionals. The study sample included a diverse range of participants from various demographic backgrounds to ensure a holistic understanding of the trust-loyalty relationship. The secondary data findings reveal that trust significantly impacts customer loyalty, with transparency, product quality, consistent customer service, and corporate social responsibility emerging as the most influential factors. Companies that prioritize these elements tend to foster stronger customer relationships and achieve higher loyalty rates. Furthermore, the study highlights the cultural and economic contexts unique to Kenya, providing insights into how local nuances affect consumer perceptions of trust and loyalty. This research contributes to the broader understanding of consumer behavior in emerging markets and offers practical recommendations for businesses aiming to improve customer retention through trust. This study was based on a major theory, The Theory of Reasoned Action (TRA) which was proposed by Martin Fishbein and leek Ajzen in 1975. This theory helps us understand different ways trust influences customer loyalty to food and beverages, especially in Kenya. The study employed a quantitative research methodology to investigate the influence of trust on customer loyalty in food companies in Kenya. This approach involved the collection and analysis of numerical data to quantify the relationship between trust and customer loyalty. Data was collected using structured questionnaires. The questionnaire was designed to measure key constructs such as trust (e.g., reliability, honesty, and competence of the company) and customer loyalty (e.g., repeat purchase behavior, willingness to recommend). The questionnaire was pre-tested to ensure validity and reliability before full-scale data collection. Collected data was analyzed using statistical software such as SPSS. This quantitative methodology provided a robust framework for understanding how trust influences customer loyalty in the context of food companies in Kenya, enabling the formulation of evidence-based recommendations for enhancing customer retention strategies.
Full - text undergraduate research project